Multifunctional and Scalable Nanoparticles for Bimodal Image-Guided Phototherapy in Bladder Cancer Treatment - Tang, Menghuan; Mahri, Sohaib; Shiau, Ya‑Ping; Mukarrama, Tasneem; Villa, Rodolfo; Zong, Qiufang; Racacho, Kelsey Jane; Li, Yangxiong; Lee, Yunyoung; Huang, Yanyu; Cong, Zhaoqing; Kim, Jinhwan; et al. (Nano-Micro Letters, 2025)
Rational design of multifunctional nanoplatforms capable of combining therapeutic effects with real-time monitoring of drug distribution and tumor status is emerging as a promising approach in cancer nanomedicine. Here, we introduce pyropheophorbide a–bisaminoquinoline conjugate lipid nanoparticles (PPBC LNPs) as a bimodal system for image-guided phototherapy in bladder cancer treatment. PPBC LNPs not only demonstrate both powerful photodynamic and photothermal effects upon light activation, but also exhibit potent autophagy blockage, effectively inducing bladder cancer cell death. Furthermore, PPBC LNPs possess remarkable photoacoustic (PA) and fluorescence (FL) imaging capabilities, enabling imaging with high-resolution, deep tissue penetration and high sensitivity for tracking drug biodistribution and phototherapy efficacy. Specifically, PA imaging confirms the efficient accumulation of PPBC LNPs within tumor and predicts therapeutic outcomes of photodynamic therapy, while FL imaging confirms their prolonged retention at the tumor site for up to 6 days. PPBC LNPs significantly suppress bladder tumor growth, with several tumors completely ablated following just two doses of the nanoparticles and laser treatment. Additionally, PPBC LNPs were formulated with lipid-based excipients and assembled using microfluidic technology to enhance biocompatibility, stability, and scalability, showing potential for clinical translation. This versatile nanoparticle represents a promising candidate for further development in bladder cancer therapy. Highlights: 1 Pyropheophorbide a–bisaminoquinoline conjugate lipid nanoparticles (PPBC LNPs), formulated with lipid-based excipients and assembled using microfluidics, exhibit excellent biocompatibility and stability, indicating promise for clinical applications. 2 PPBC LNPs possess remarkable photoacoustic and fluorescence imaging capabilities, enabling high-resolution, deep tissue penetration and high sensitivity imaging for tracking drug biodistribution and phototherapy efficacy.